Promotion and Marketing Communications (IntechOpen, 2021)
This edited Promotion and Marketing Communications book is an original volume that presents a collection of chapters authored by various researchers and edited by marketing communication professionals. To survive in the competitive world, companies feel an urge to achieve a competitive advantage by applying accurate marketing communication tactics. Understanding marketing communication is an essential aspect for any field and any country. Hence, in this volume there is the latest research about marketing communication under which marketing strategies are delicately discussed. This book does not only contribute to the marketing and marketing communication intellectuals but also serves different sector company managerial positions and provides a guideline for people who want to attain a career in this field, giving them a chance to acquire the knowledge regarding consumer behavior, public relations, and digital marketing themes.